A simple quantitative and qualitative microbiological screening test for bacteriuria. Issue 6 (November 1969) - Mackay-Scollay, E. M.
Abstract : A simple, accurate screening test for significant bacteriuria is described. It entails brief contact of a freshly voided specimen of urine with the surface of a solid culture medium lining the wall of a transparent disposable plastic container, incubating it at 37°C for 24 hours, and counting colonies developing on a proscribed surface area. The method obviates errors due to contaminants, affords a limited species differentiation of the causative organisms, and provides a ready means of obtaining a direct sensitivity test on the responsible bacteria.